The mediating role of whistleblowing as mediation on the effect of organizational commitment on employee fraud - Nataliana Bebasari; Muhammad Sapruwan (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the effect of organizational commitment on employee fraud with whistleblowing intention as a mediating variable. The research sample was 82 permanent employees of companies in Bekasi who worked for at least 1 year. Sampling using non-probability sampling technique type purposive sampling. The research data were processed with SmartPLS. The results showed that organizational commitment affects employee fraud. Organizational commitment also affects whistleblowing intention. Meanwhile, whistleblowing intention affects employee fraud. Thus, whistleblowing intention mediates the effect of organizational commitment on employee fraud in company employees in Bekasi.